Harmonisasi Hukum Waris Islam, Hukum Adat dan Hukum Nasional Telaah Normatif terhadap Kompilasi Hukum Islam, Hukum Adat dan KUHPerdata - Salas, Maizidah; Wardani, Susilo; Suroso, Teguh (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
The inheritance system in Indonesia is governed by three main legal frameworks: Islamic law, customary (adat) law, and national law. Each of these systems has its own unique characteristics and principles of distribution. This study aims to explore how Islamic inheritance law, customary law, and national inheritance law in Indonesia are harmonized with one another and how inheritance distribution is regulated under these three legal systems. The research method used in this study is normative juridical, focusing on the applicable legal provisions. The findings indicate that the Compilation of Islamic Law (KHI) stipulates inheritance distribution based on Sharia principles, granting a larger share to male heirs. In contrast, customary law emphasizes cultural values and diverse kinship systems, while the Indonesian Civil Code (KUHPerdata) provides a more formal and balanced distribution between male and female heirs. Although these three systems operate concurrently, they are not always harmonious, requiring legislative efforts and jurisprudence to align inheritance regulations in order to achieve social justice and legal certainty amidst Indonesia’s legal pluralism.